Pengelolaan Sesi Latihan Bola Voli: Rencana Mikro, Monitoring Beban, dan Recovery - Sahabuddin (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The management of volleyball training sessions among collegiate athletes faces complex challenges due to the lack of integrated scientific approaches, which may reduce training effectiveness and increase the risk of fatigue and injury. This study addresses the suboptimal implementation of periodization-based microcycle planning, training load monitoring, and recovery strategies within a unified system. The objective of this research is to examine the effectiveness of an integrated training management model in improving athletes’ performance and physiological condition. A quasi-experimental method with a pretest–posttest control group design was employed, involving 40 collegiate athletes over an eight-week period. The results indicate that the experimental group showed significant improvements in countermovement jump by 12.2% and spike reach by 3.1%, accompanied by a reduction in sRPE by 11.5% and an increase in recovery scores by 22.5%, while the control group demonstrated no meaningful changes. These findings suggest that the integration of microcycle planning, internal and external load monitoring, and structured recovery strategies enhances physiological efficiency, neuromuscular adaptation, and the sustainability of athletic performance. The study concludes that the integrated training management model is more effective than conventional approaches as it enables objective and systematic control of training intensity. The novelty of this research lies in the development of an integrated training session management model that combines three key components in an applicable, practical, and context-appropriate manner for collegiate athletes, thereby bridging the gap between sport science theory and coaching practice.